I Study to be an Engineer. Why to Study Administration and Accounting? - Damián Simón, Javier (2018)
Currently, cross-cutting subjects are promoted in the engineering curriculum to give added value to their graduates and to meet the new demands of the labor market. The main objective of the research work was to know the opinions of the engineering students about the level of contribution of the administrative-economic subjects in their academic training. Through a descriptive study with a qualitative approach, opinions of 23 engineering students were studied. These students studied administration and accounting subjects, which are part of the curriculum, during a year. It was found that the students show a very marked development of their professional identity as engineers, which determines their acceptance level of the subjects different from their professional profile, since they think they are useless. However, when the teachers adequately select the didactic resources and the teaching process adjusted to an engineering profile, students start to recognize the contribution of these subjects to their university education, which provide them with the foundations to face the new demands as future engineers in not only technical activities.